2006
DOI: 10.1002/14651858.cd004750.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Superficial heat or cold for low back pain

Abstract: Analysis 3.5. Comparison 3 Heat plus exercise vs other interventions (acute and sub-acute LBP <3 months), Outcome 5 Function-Roland-Morris (change values-lower score favours heat)-vs exercise alone.. .. .. .. . Analysis 3.6. Comparison 3 Heat plus exercise vs other interventions (acute and sub-acute LBP <3 months), Outcome 6 Function-MTAP (change values-higher score favours heat)-vs exercise alone.. .. .. .. .. .. Analysis 3.7. Comparison 3 Heat plus exercise vs other interventions (acute and sub-acute LBP <3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 53 publications
3
58
1
9
Order By: Relevance
“…In their study, exercise was more effective on pain relief and functional improvement [20]. In another study, cryotherapy and thermotherapy as therapeutic methods in the patients with acute and chronic low back pain had an equal effect on relieving the pain based on evaluative and descriptive measures [12], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In their study, exercise was more effective on pain relief and functional improvement [20]. In another study, cryotherapy and thermotherapy as therapeutic methods in the patients with acute and chronic low back pain had an equal effect on relieving the pain based on evaluative and descriptive measures [12], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…In most studies, thermotherapy and cryotherapy were effective, in long term, on pain relief in the patients suffering from low back pain [12,16,20]. In this regard, a study by Khadilkar et al, on treatment of chronic low back pain indicated that keeping the pain site warm (wrapped up by a blanket) for a long term in the patients with chronic low back pain reduced the pain efficiently [16].…”
Section: Discussionmentioning
confidence: 99%
“…11 Medication Plain analgesic drugs such as acetaminophen and nonsteroidal anti-inflammatory drugs (NSAIDs) are effective and recommended for pain control. There is evidence that NSAIDs are first-line drugs for pain control.…”
Section: Patient Advicementioning
confidence: 99%
“…There is evidence from systematic reviews to support the use of superficial heat (benefit over placebo, acetaminophen or ibuprofen), 5 spinal manipulation (benefit over sham therapy), 6 massage (benefit over inactive control) 7 and acupuncture (benefit over no treatment) 8 in patients with acute low-back pain. For flexion-aggravated low-back pain, home exercises are indicated and should include repeated passive extension in the lying position progressing to standing (see link to CORE Back Tool and other useful tools in Appendix 1, available at www.cmaj.ca/lookup/suppl/doi:10 .1503/cmaj.150660/-/DC1).…”
Section: What Nonpharmacologic Therapy Should Be Prescribed For This mentioning
confidence: 99%